Popular culture in Mario de Andrade´s archives: "Na pancada do Ganzá" and "Os Fundos Villa-Lobos"Popular culture in Mario de Andrade´s archives: "Na pancada do Ganzá" and "Os Fundos Villa-Lobos" - Lopes, Beatriz (2014)
Aware that he lived in a world increasingly directed to the disappearance of cultural authenticity, Mário de Andrade longed for taking forward a project to preserve the "authenticity" of Brazilian culture, so he plans, outlines, organizes their collections and studies, and initiates the scriptures of his "great" work, Na pancada do Ganzá. For the purposes of this article, that it is proposed to indicate the possibilities of a new cultural dialogue between Mário de Andrade, artists and popular musicians, including Pixinguinha, we present a short summary of what was advertised on archival research and works that endorse the musicologist's project, Na pancada do Ganzá and Fundos Villa- Lobos collection poetic-musical contained therein.